EFL Students’ Perception of Using Audio Visual Media in Listening Class - Salma Fadlina Laus; Karmila Machmud; Nurlaila Husain (Transbahasa, 2025)
Perception is a complex cognitive process involving the recognition, organization and interpretation of sensory information in order to understand and respond to the environment, which is influenced by each individual's personal experience and background. In the context of language learning, students' perception of learning media plays an important role in determining the effectiveness of the learning process. The purpose of this study is to describe EFL students' perceptions of the use of audio-visual media in listening learning. This study used a qualitative approach with descriptive method. Data were collected through an open questionnaire distributed to 13 fourth semester students of the English Education Study Program at Gorontalo State University who had taken the Listening for Professional Context and Academic Purpose course. The results showed that the majority of students had a positive perception of audio-visual media. They consider this media effective in improving understanding of listening material. Helps recognize English accents and intonations, and creates a more interesting and less boring learning atmosphere. However, some challenges were also found, such as the duration of the video that was too long, the technical quality of the media that was less than optimal, and the tendency to rely too much on visual aspects. Overall, audio-visual media is a very potential learning tool if applied strategically and proportionally in listening classes. These findings are expected to contribute to the development of listening teaching strategies that are more effective and in accordance with the needs of EFL students.